Terminology : theory, methods, and applications - Cabré, M. Teresa (Maria Teresa) (Terminology and lexicography research and practice, 1999)
Terminology: Theory, methods and applications addresses language specialists, terminologists, and all those who take an interest in socio-political and technical aspects of Terminology. The book covers its subject comprehensively and deals among other things with concepts (the relation between linguistics, cognitive science, communication studies, documentation and computer science); Methodology, especially with regard to specialised language and dictionaries; the social-political challenges of the modern technological society and some solutions from a Terminological point of view; Term.